Study on Equlibrium Constant of Ion Exchange Reaction Involving CI-/I- Uni-Univalent Ion Exchange System in the Strongly Basic Anion Exchanger Amberlite IRA-400 - Lokhande, R.S.; Singare, P.U. (Asian Journal of Chemistry, 2010)
A known amount of ion exchange resin in chloride form was allowedto reach equilibrium with potassium iodide solution of five different concentrationsat a specified temperature. The equilibrium concentrations ofthe chloride and iodide ions in the solution as well as in the resin phaseare determined. From these measurements the equilibrium constant (k) andenthalpy of ion exchange reaction were calculated.